Prevalencia de parasitosis intestinal portrichuris trichiura en pacientes pediátricos. - Chuya Tapia, Leidy Mishelle (Machala : Universidad Técnica de Machala, 2022)
Introduction: The study of intestinal parasitosis has great relevance worldwide, the WHO stated that 46 million infants are infected by helminths, 13 million include children aged 1-4 years and 33.3 million schoolchildren aged 5-14. years, in addition to identifying socio-cultural factors that trigger pathologies, taking into account health measures to improve living conditions, delimiting the pediatric group, because its incidence generates rates of anemia, physical decline, weight loss, among other manifestations clinics. The main objective is to determine the prevalence of Trichuris trichiura in pediatric patients through a clinical study carried out by the pharmaceutical biochemist to know the clinical manifestations caused by helminth infections. Methodology: The bibliographic-descriptive methodology was used, carrying out bibliographic reviews on the information on the intestinal parasitism of Trichuris trichiura through reliable sources such as scientific articles and books. Conclusion: It was possible to determine through the bibliographical compilation the percentage of the prevalence of Trichuris trichiura based on the evaluation of people who go to clinical laboratories to perform routine tests, of which 45% show positive results, especially pediatric patients who go to public health centers, in the same way in private laboratories there are 25% of parasitic conditions due to helminths, due to the lack of knowledge of hygienic-sanitary measures regardless of social class, since this parasitic infection is caused by a bad hygiene habit, contaminated food and poor processing of the drinking water system.
Introducción: El estudio de la parasitosis intestinal tiene gran relevancia a nivel mundial, la OMS manifestó que 46 millones de infantes se ven infectados por helmintos, 13 millones incluyen a niños de 1-4 años y 33,3 millones a escolares de 5-14 años, además de identificar factores socio-culturales que desencadenan las patologías, tomando en cuenta medidas sanitarias para mejorar las condiciones de vida, delimitando al grupo pediátrico, debido que su incidencia genera índices de anemia, decaimiento físico, pérdida de peso, entre otras manifestaciones clínicas. El principal objetivo es determinar la prevalencia de Trichuris trichiura en pacientes pediátricos a través de un estudio clínico realizado por el bioquímico farmacéutico para conocer las manifestaciones clínicas causadas por infecciones del helminto. Metodología: Se empleó la metodología de tipo bibliográfica-descriptiva realizando revisiones bibliográficas sobre la información del parasitismo intestinal de Trichuris trichiura mediante fuentes confiables como artículos científicos y libros. Conclusión: Se pudo determinar mediante la recopilación bibliográfica el porcentaje de la prevalencia de Trichuris trichiura en base a la evaluación de personas que acuden a los laboratorios clínicos a realizarse exámenes rutinarios, de los cuales el 45% arrojan resultados positivos especialmente pacientes en edad pediátrica que acuden a centros de salud pública, de la misma forma en laboratorios privados se presenta un 25% de afecciones parasitarias por helmintos, debido al desconocimiento de las medidas higiénico-sanitarias indistintamente de la clase social, ya que esta infección parasitaria se da por un mal hábito de higiene, alimentos contaminados y el mal procesamiento del sistema de agua potable.
Keywords: PARASITOSIS INTESTINAL; PREVALENCIA; PACIENTES PEDIATRICOS; TRICHURIS TRICHIURA